Syndromes of corruption wealth, power, and democracy - Johnston, Michael (Cambridge Cambridge University Press, 2005)
Corruption is a threat to democracy and economic development in many societies. It arises in the ways people pursue, use and exchange wealth and power, and in the strength or weakness of the state, political and social institutions that sustain and restrain those processes. Differences in these factors, Michael Johnston argues, give rise to four major syndromes of corruption: Influence Markets, Elite Cartels, Oligarchs and Clans, and Official Moguls. Johnston uses statistical measures to identify societies in each group, and case studies to show that the expected syndromes do arise.
Includes bibliographical references (p. 228-256) and index.
Keywords: Corruption